The Implementation of Intensification Buras Chicken to Increase the Fishermen Income - Hafid, Harapin; Patriani, Peni; Ananda, Siti Hadrayanti; Aslan, L.M.; Nuraini (Talenta Publisher Universitas Sumatera Utara, 2019)
Fisherman family in coastal area is one of the groups who raise chicken in general, because it is easy to take care, eventhough it is still in extensification level. Approach methodology used is bay : (1) Speech and discussion on potency, prospect, and benefit of raising chicken, (2) demonstration and guidance for working chicken coop, ration formula, tetelo vaccination and choosing a new generation, (3) guidance of raising Buras chicken, time after harvesting and marketing, (4) forming a raise chicken group in order to discus in development of business and carrying out their problem. Speech and discussion material presented is positively responded and satisfactory to the participants because there has not yet been carried out such this program. Generally, the participants wanted to adopt and they were active in demonstration on choosing new generation, ration formula, prohibition of disease, taking care of chicken, making of coop and equipment, timing of harvesting and marketing. It would be concluded that the participants who came from Kelurahan Nambo is very enthusiasm and active in this program. Generally, the participants wanted to raise chicken as a primary job as well as their farming.